Broadly reactive human CD8 T cells that recognize an epitope conserved between VZV, HSV and EBV. - Christopher Chiu; Megan McCausland; John Sidney; Fuh-Mei Duh; Nadine Rouphael; Aneesh Mehta; Mark Mulligan; Mary Carrington; Andreas Wieland; Nicole L Sullivan; Adriana Weinberg; Myron J Levin; et al. (PLoS Pathogens)
Human herpesviruses are important causes of potentially severe chronic infections for which T cells are believed to be necessary for control. In order to examine the role of virus-specific CD8 T cells against Varicella Zoster Virus (VZV), we generated a comprehensive panel of potential epitopes predicted in silico and screened for T cell responses in healthy VZV seropositive donors. We identified a dominant HLA-A*0201-restricted epitope in the VZV ribonucleotide reductase subunit 2 and used a tetramer to analyze the phenotype and function of epitope-specific CD8 T cells. Interestingly, CD8 T cells responding to this VZV epitope also recognized homologous epitopes, not only in the other α-herpesviruses, HSV-1 and HSV-2, but also the γ-herpesvirus, EBV. Responses against these epitopes did not depend on previous infection with the originating virus, thus indicating the cross-reactive nature of this T cell population. Between individuals, the cells demonstrated marked phenotypic heterogeneity. This was associated with differences in functional capacity related to increased inhibitory receptor expression (including PD-1) along with decreased expression of co-stimulatory molecules that potentially reflected their stimulation history. Vaccination with the live attenuated Zostavax vaccine did not efficiently stimulate a proliferative response in this epitope-specific population. Thus, we identified a human CD8 T cell epitope that is conserved in four clinically important herpesviruses but that was poorly boosted by the current adult VZV vaccine. We discuss the concept of a "pan-herpesvirus" vaccine that this discovery raises and the hurdles that may need to be overcome in order to achieve this.